2021
DOI: 10.35808/ersj/2431
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 on Road Freight Transport Evidence from Poland

Abstract: Purpose:The main aim of this article is to investigate the impact of the COVID-19 pandemic on the Polish road freight transport industry. This paper seeks to understand the impacts on travel behavior and the transport system caused by the different actions and policies adopted by the governments and transport authorities to contain the COVID-19 spread. Design/Methodology/Approach: Econometric and statistical methods were used, including analysis of primary data, predictive model of exponential smoothing. Findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 35 publications
0
5
0
1
Order By: Relevance
“…Nwaeze G. також підкреслює виклики, з якими стикається транспортна галузь у всьому світі, оскільки пандемія спричинила перебої та створила значні перешкоди [8]. Лацка І. і Перкуміене Д. надають конкретне розуміння впливу COVID-19 на вантажні автомобільні перевезення та логістику і транспортну галузь, відповідно, підкреслюючи необхідність стратегічного планування та потенціал для прогресу в цьому секторі [9,10]. Ці дослідження разом підкреслюють серйозний вплив пандемії на українську транспортну галузь та економіку в цілому.…”
Section: № 11 2024unclassified
“…Nwaeze G. також підкреслює виклики, з якими стикається транспортна галузь у всьому світі, оскільки пандемія спричинила перебої та створила значні перешкоди [8]. Лацка І. і Перкуміене Д. надають конкретне розуміння впливу COVID-19 на вантажні автомобільні перевезення та логістику і транспортну галузь, відповідно, підкреслюючи необхідність стратегічного планування та потенціал для прогресу в цьому секторі [9,10]. Ці дослідження разом підкреслюють серйозний вплив пандемії на українську транспортну галузь та економіку в цілому.…”
Section: № 11 2024unclassified
“…The articles found largely focused on specific geographic areas: countries-Colombia, France, Greece, Denmark, Italy, Slovakia, Ireland, Argentina, Austria, China (three times), Germany, Russia, India and Brazil (two times each), as well as cities: New York, Budapest, Bologna and London. There were six articles on Poland that were the most relevant to the subject of the authors' research, and only two of them concerned the impact of the COVID-19 pandemic on Polish road carriers in the light of the authors' own research (Łącka & Suproń, 2021;Nicodeme, 2023;Osińska & Zalewski, 2023;Romanow & Frąś, 2022;Świtała & Łukasiewicz, 2021). Osińska and Zalewski (2023), in their empirical analysis based on survey data made in July 2020 on 500 road transport enterprises, showed that this specific branch, which is very sensitive to changes in global trade, suffered much from the COVID-19 pandemic because:…”
Section: The Impact Of the Covid-19 Pandemic On Polish Road Transport...mentioning
confidence: 99%
“…In the second year, adaptation measures were put in place to partially recover lost passenger traffic. For freight transport, the blockade on the European economy had a negative impact on the short-term operations of transport companies [26]. In the long term, the situation was favourable because, for example, the number of kilometres travelled by road transport increased.…”
Section: Impact Of Covid-19 On Logistics and Supply Chainsmentioning
confidence: 99%